Effects of alternative framing on the publics perceived importance of environmental conservation - Sorensen, Amanda E.; Clark, Daniel; Jordan, Rebecca C. (Frontiers in Environmental Science, 2015)
Effective communication of science to the general public is important for numerous reasons, including support for policy, funding, informed public decision making, among others. Prior research has found that scientists participating in public policy and public communication must frame their communication efforts in order to connect with audiences. A frame is the mechanism that individuals use to understand and interpret the world around them. Framing can encourage specific interpretations and reference points for a particular issue or event; especially when meaning is negotiated between the media and public audiences. In this study, we looked at the effect of framing within an environmental conservation context. To do this we had survey respondents rank common issues, among them being environmental conservation, from most important to least important for the government to address. We framed environmental conservation using three synonymous terms (environmental security, ecosystem services, and environmental quality) to assess whether there was an effect on rankings dependent on how we framed environmental conservation. We also investigated the effect of individuals’ personality characteristics (identity frame) on those environmental conservation rankings. We found that individuals who self-identified as environmentalist were positively associated with ranking highly (most important) environmental conservation when it was framed as either environmental quality or ecosystem services, but not when it was framed as environmental security. Conversely, those individuals who did not rank themselves highly as self-identified environmentalists were positively associated with environmental conservation when it was framed as environmental security. This research suggests that framing audience specific messages can engender audience support in hot-button issues such as environmental conservation and climate change.